THE DOBROGEA WALLS IN THE WRITINGS OF THE POLISH DIPLOMATS ERAZM OTWINOWSKI (1557) AND ANDRZEJ TARANOWSKI (1569) - Richard Mason (Journal of Ancient History and Archaeology, 2018)
The travelogues of the sixteenth-century Polish diplomats Erazm Otwinowski and Andrzej Taranowski are important, but as yet overlooked sources on the Dobrogea walls as well as on local geography and toponymy. They represent the earliest Western sources for the Dobrogea walls and contain the first pre-modern mention of the forts which are an important feature of these defensive structures. Despite their value, however, these sources have not yet been included in the discussion of the history of the Dobrogea walls. The present paper considers the history of these documents and attempts to place them in the context of the contemporary Polish and German literature. Annotated excerpts from the original Polish and Germans texts together with an English translation will facilitate use of these sources by researchers. They will contribute to our understanding of the history and state of preservation of the Dobrogea walls in a period for which we are otherwise not well informed.